PERLINDUNGAN HUKUM TERHADAP INVESTOR PEMEGANG SAHAM PADA EMITEN DITINJAU DARI HUKUM KEPAILITAN DAN HUKUM PERSEROAN TERBATAS (STUDI KASUS NO.4/PDT.SUS.PEMBATALAN PERDAMAIAN/2019/PN.NIAGA.JKT.PST JUNCTO NO.1/PK/PDT.SUS-PAILIT/2020) - Fernando Chandra; Mariske Myeke Tampi (Jurnal Hukum Adigama, 2021)
The capital market has a function as a means of financing that brings together investors as parties who have more funds with issuers, namely those who are in need of funds. The object that becomes an instrument in buying and selling activities on the capital market is in the form of securities which are often called securities. Legal protection for investors still has many weaknesses, both juridically normative and empirical. The number of regulations and legal regimes involved in the company bankruptcy event creates legal uncertainty for investor protection. Considering the failure of regulators to observe developments that occur or not adapting quickly to rapid developments, investors may abandon the capital market in Indonesia. In order to achieve the objectives of the capital market, namely to meet the needs of business players' funds, a legal protection mechanism is needed that can make potential investors feel safe investing in the capital market. Both the UUPM, UUPT and UUKPKPU regimes have provided an opportunity for capital market players, especially investors, to save their assets when bankruptcy occurs.